Temperature-sensitive mutants of vesicular stomatitis virus are conditionally defective particles that interfere with and are rescued by wild-type virus. - Youngner, J S (1976)
Temperature-sensitive (ts) mutants of vesicular stomatitis virus belonging to complementation groups I, II and IV inhibited the replication of wild-type vesicular stomatitis virus when mixed infections were carried out in BHK21 cells at 32, 37, and 39.5 C. The group IV mutant (ts G 41) was most effective in this regard; wild-type virus yields were inhibited almost 1,000-fold in mixed infections with this mutant at 32 C. In the case of group I and II mutants, inhibition of wild-type virus replication at 37 and 39.5 C was accompanied by an enhancement (up to 15,000-fold) of the yields of the coinfecting ts mutant. The yields of the group IV mutant (ts G 41) were not enhanced by mixed infections with wild-type virus at any temperature, although this mutant inhibited wild-type virus replication at all temperatures. The dominance of the replication of ts mutants at 37 C provides a rationale for the selection and maintenance of ts virus in persistently infected cells.